Effective food and nutrition policy responses to HIV/AIDS: what we know and what we need to know - Haddad, Lawrence J.; Gillespie, Stuart (International Food Policy Research Institute, 2001)
The impact of human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) on people’s lives and on development is staggering. Millions have died and livelihoods have been devastated, particularly in Sub-Saharan Africa. Agriculture and natural resources are important components of such livelihoods. And the nutritional status of those infected and affected plays a large part in determining their current welfare and their ability to further develop their livelihoods towards activities that help to mitigate the impacts of AIDS and prevent the spread of HIV. This paper first reviews the potential pathways through which HIV/AIDS affects assets and institutions generally and then the specific impacts on agriculture, natural resource management, food security, and nutrition. The review addresses the question of how the public sector can and should respond to these challenges. The focus is primarily on mitigation, though the authors note that effective mitigation can also serve as a very cost-effective form of prevention. As labor becomes depleted, new cultivation technologies and varieties need to be developed that do not rely so much on labor, yet allow crops to remain drought resistant and nutritious.